The Role of Lexical Cohesion in Improving Twelfth Graders’ Essay Writing Quality - Khalil, Abdelhamid A. (2023)
This open access book presents contributions on a wide range of scientific areas originating from the BUiD Doctoral Research Conference (BDRC 2022)